PENGARUH KOMPETENSI TERHADAP KINERJA AUDITOR PADA INSPEKTORAT KABUPATEN MUNA BARAT - Sahidin Nurdin; Nasrullah Dali (Tamilis Synex: Multidimensional Collaboration, 2025)
The competencies in question include professional knowledge, technical skills, work attitude and ethics, communication skills, and problem-solving abilities. This research uses a quantitative approach with a census method involving all employees of the Inspectorate of West Muna Regency as respondents. Data were collected through the distribution of questionnaires and analyzed using simple linear regression. The results of the study indicate that competence has a positive and significant effect on auditor performance. The coefficient of determination value of 47.2% indicates that competence explains nearly half of the variation in auditor performance. These findings highlight the importance of enhancing competence as a strategic effort to improve auditor performance and ensure regional financial accountability.